PTPTN wipes out national hero's loan debt - New Sarawak, Tribune (New Sarawak Tribune, 2013)
KANGAR: The National Higher Education Fund Corporation (PTPTN) has wiped out the study-loan debt of national hero, ASP Zulkifli Mamat, who was killed while defending the country's sovereignty in Lahad Datu, Sabah last month.